(untitled) (Research Announcements "Heritage BG", 2025)
The ancient cities of Aegean Thrace—region between Nestos and Hebros Rivers—began issuing silver coins of various denominations almost immediately after their founding. This not only affirmed their status as city-states but also demonstrated their direct access to Thrace’s abundant and renowned precious metal reserves, deposits that according to archaeological evidence were likely being exploited as early as the late 6th century BC. This study provides insights into the region’s historical metallurgy and economy and aims to evaluate the quality of the silver used in these coins by analysing their chemical composition and comparing different chronological phases.